Study on several novel topological phases in sonic wave systems - Cheng, Zheyu (Nanyang Technological University, 2025)
A phase transition occurs when the order parameter changes, such as in the case of ice melting into water or paramagnets changing into ferromagnets. In 2016, David J. Thouless, F. Duncan M. Haldane, and J. Michael Kosterlitz won the Nobel Prize in Physics for their pioneering work on topological phase transitions. Unlike conventional phases, which are characterized by order parameters, topological phases are described by topological invariants. Due to the novelty of topological phases, extensive research has been conducted on the topological phases of matter, ranging from condensed matter physics to photonics, phononics, and circuits. Because experiments in electronic systems are extremely challenging, many topological matter models have been demonstrated in classical wave systems, such as photonics and acoustics. The discovery of new topological phases opens up possibilities for new theories and novel applications. In this thesis, I study several novel topological phases in acoustic systems, including experimental demonstrations of three-dimensional Landau levels, π/2 modes in the Floquet system, and disorder-induced skin effects.